Circular : Interview with Lord Halifax - Citrine, Walter, 1887-1983
012a-0100-001 Telegraphic Address: TRADUNIC. SOWEST LONDON Telephone VICTORIA 9020 The Trades Union Congress General Secretary, SIR WALTER CITRINE K.B.E. (To whom all communications should be addressed) Your ref- Our Ref: WMC/WJB/AC/455 Department International TRANSPORT HOUSE, SMITH SQUARE, LONDON. S.W.1. 14th April, 1938. TO ALL MEMBERS OF THE GENERAL COUNCIL. Dear Sir/Madam, INTERVIEW WITH LORD HALIFAX. CONFIDENTIAL. Herewith I enclose report between Lord Halifax and members of General Purposes Committee. The interview was arranged at very short notice, as a result of the receipt of an urgent telegram from the Spanish T.U.C, asking for some definite action to be taken to get the arms embargo withdrawn. I communicated with the Chairman and the members of the Committee, and they agreed it would be advisable, in the circumstances, to approach the Foreign Secretary without delay. He agreed to have a meeting, and it was understood that it should be kept strictly private, so that he could speak to the deputation with freedom. Yours faithfully, WALTER CITRINE. General Secretary. Report. 292/946/12a/100